The legal basis of Sami reindeer herding rights in Sweden - Torp, Eivind (Arctic Review on Law and Politics, 2013)
This article discusses the basis of the Sami right to pursue reindeer herding, and how that right has been regulated in law. Two aspects of this right are particularly significant: establishing which land areas are covered by the reindeer herding right and clarifying what the right entails. The legal institution of ‘immemorial prescription’ has long been considered highly significant in judicial trials concerning the reindeer herding rights. In the wake of a ruling by the Swedish Supreme Court, that picture has now changed.Keywords: Sami reindeer herding, customary law, immemorial prescription, occupation, Swedish Supreme Court.Citation: Arctic Review on Law and Politics, vol. 4, 1/2013 pp. 43–61. ISSN 1891-6252